Pooled CRISPR screens in Drosophila cells - Viswanatha, Raghuvir (Curr Protoc Mol Biol, 2019)
High-throughput screens in Drosophila cell lines have led to discovery of conserved gene functions related to signal transduction, host-pathogen interactions, ion transport, and more. CRISPR/Cas9 technology has opened the door to new types of large-scale cell-based screens. Whereas arrayed-format screens require liquid handling automation and assay miniaturization, pooled-format screens, in which reagents are introduced at random and in bulk, can be done in a standard lab setting. We provide a detailed protocol for conducting and evaluating genome-wide CRISPR single guide RNA (sgRNA) pooled screens in Drosophila S2R+ cultured cells. Specifically, we provide step-by-step instruction for library design and production, optimization of cytotoxin-based selection assays, genome-scale screening, and data analysis. This type of project takes about three months to complete. Results obtained in this type of screen can be used in follow-up studies performed in vivo in Drosophila, mammalian cells, and/or other systems.